Four-Element Microstrip Patch Array Antenna with Corporate-Series Feed Network for 5G Communication - Janam Maharjan; Dong-You Choi (International Journal of Antennas and Propagation)
The paper proposes a simple four-element microstrip patch array antenna fed with corporate-series technique. The paper compares the proposed design with four-element antennas fed with only series-fed and corporate-fed microstrip antennas. All three antenna designs use rectangular microstrip patch elements with two insets and slots on both sides of the patch. The patch elements are accompanied by Yagi elements: three director elements and two reflector elements. Through comparison of simulation results, the paper shows that four-element array antenna with combined corporate-series feeding technique performs better compared to antennas with only either series or corporate feeding network. The proposed corporate-series fed antenna achieves better performance with wide frequency bandwidth of 25.04–30.87 GHz and gain of 9.5 dB. The antenna has an end-fire radiation pattern. Overall performance shows that the proposed corporate-series-fed microstrip patch antenna with Yagi elements is suitable for next generation 5G communication.